Controlled Synthesis of Organic/Inorganic van der Waals Solid for Tunable Light–Matter Interactions. (27th October 2015) - Niu, Lin; Liu, Xinfeng; Cong, Chunxiao; Wu, Chunyang; Wu, Di; Chang, Tay Rong; Wang, Hong; Zeng, Qingsheng; Zhou, Jiadong; Wang, Xingli; Fu, Wei; Yu, Peng; et al.
Abstract : High‐quality organic and inorganic van der Waals (vdW) solids are realized using methylammonium lead halide (CH3 NH3 PbI3 ) as the organic part (organic perovskite) and 2D inorganic monolayers as counterparts. By stacking on various 2D monolayers, the vdW solids exhibit dramatically different light emissions. Futhermore, organic/h‐BN vdW solid arrays are patterned for red‐light emission.